Islamic Education in the Era of Technological Wave: A Case in Indonesia Today - Arif Rahman (International Islamic Schools Alliance, 2016)
The long journey of Islamic educational reform has come a new phase, in which Islamic education is no longer bound by the dichotomy paradigm or the Islamization of Science. But faced with a huge wave of technology that has touched all aspects of human life. Indonesia has turned into a market for technology companies of the world, but Islamic education has not been seen by intelligently utilizing current technological developments, as an integrated part in solving the problems that have not been able to be resolved in Islamic education itself. The dynamics of the encounter of technology to Islamic educational dimension in the case in Indonesia shows that the need for serious efforts to capitalize on opportunities both as a form of effective collaboration.